Characteristics and Influence of Marketing Information in the Poverty Relief e-Commerce Platform - FAN Zhenjia, WANG Xuan, LIAO Zixuan (Nongye tushu qingbao xuebao, 2020)
[Purpose/Significance] E-commerce platforms take critical part in the promotion of the sale of agricultural products in poor areas and achieve poverty alleviation goals. It is essential to identify the characteristics and influences of the marketing information in the platforms and will provide a realistic reference for the establishment of sustainable targeted poverty alleviation. [Method/Process] Based on qualitative data collected from three typical WeChat e-commerce platforms, characteristics of marketing information have been concluded. Besides on the basis of constructing the experimental design and the interview to college students, the influence and sustainability of different approaches has been discussed. [Results/Conclusions] There are at least six marketing approaches, including promotion marketing, health marketing, star marketing, direct marketing, news marketing and emotional marketing. As for college students, the effects of different marketing methods vary greatly, and emotional marketing may lead to the deviation of poverty alleviation discourse, and there is a risk of trust crisis of poverty alleviation and rural assistance if emotional marketing is abused.